Japanese Teachers’ Attitudes and Self-Efficacy Toward Inclusive Education: Three-Way ANOVA and Regression Analyses - Oo, Zun Wai; KAWAI, Norimune; MATSUMIYA, Nagako; HAYASHIDA, Masashi (Journal of Education for Sustainability and Diversity, 2024)
In the last two decades, interest in inclusive education has grown, and researchers have begun to study teachers’ attitudes toward it. However, few studies have examined both pre-service and in-service teachers’ perspectives, particularly in Japan. Therefore, the current study contributed to investigating the attitudes and self-efficacy of pre-service and in-service teachers toward inclusive education in Japan. A descriptive survey was used to collect data for quantitative analysis. Firstly, no significant main effects and interactions of attitudes were found for all independent variables. Next, it was found that there were two main effects on the self-efficacy scale: training and prior contact with disabilities. Finally, two predictors for the attitude scale were found: self-efficacy and training in inclusive education and special needs education. These results implied a better understanding of the attitudes and self-efficacy of pre-service and in-service teachers. They provided insight into how to improve teacher training for inclusive quality education for all, as envisioned by SDG 4.